Tingkat Keberhasilan Implementasi Program Rujuk Balik pada Pasien Penyakit Kronis di Puskesmas - Al'fadiyah, Lola; Solida, Adila; Wardiah, Rizalia (FORIKES, 2025)
The referral program is a program to improve the quality of health services for participants of the Social Security Administering Body for Health and facilitate access to health services for participants suffering from chronic diseases. Community health centers often receive referrals, but not all health centers utilize the referral program optimally and result in a low number of participants in the referral program. The purpose of this study was to analyze the implementation of the referral program for chronic disease patients in community health centers. This study was a qualitative study, involving 6 informants, consisting of 1 person in charge of the referral program, 2 program implementing officers, 1 head of the community health center, and 2 patients of the referral program. Data collection techniques were carried out through in-depth interviews, observation and document studies, then analyzed narratively. The results of the analysis on the input aspect showed that man was not optimal due to the lack of program management staff; mandatory materials were not all adequate; machines still need to be increased, especially computers for services. In the process aspect, the registration process for participants was assisted by officers and given a referral letter to the community health center in a stable condition, while the eligibility letter can also be seen from proof of participation, but officers did not understand the form of the eligibility letter. In conclusion, the problematic input aspect is a lack of manpower, materials, and machinery, which disrupts the process aspect, such as the suboptimal performance of the referral program managers in providing services.Keywords: referral program; chronic disease; input; process ABSTRAK Program rujuk balik merupakan program untuk meningkatkan mutu pelayanan kesehatan bagi peserta Badan Penyelenggara Jaminan Sosial Kesehatan dan mempermudah akses pelayanan kesehatan bagi peserta yang menderita penyakit kronis. Puskesmas sering menerima rujukan balik, namun tidak semua puskesmas menggunakan program rujukan secara optimal dan menyebabkan rendahnya jumlah peserta program rujuk balik. Tujuan penelitian ini adalah menganalisis implementasi program rujuk balik pada pasien penyakit kronis di puskesmas. Penelitian ini merupakan studi kualitatif, yang melibatkan 6 informan, terdiri atas 1 orang penanggung jawab program rujuk balik, 2 orang petugas pelaksana program rujuk balik, 1 orang kepala puskesmas, dan 2 orang pasien program rujuk balik. Teknik pengumpulan data dilakukan dengan wawancara mendalam, observasi dan studi dokumen, lalu dianalisis secara naratif. Hasil analisis pada aspek input menunjukkan bahwa man belum optimal karena masih kurangnya tenaga pengelola program; material yang wajib belum semuanya memadai; machines masih perlu diperbanyak terutama komputer untuk pelayanan. Pada aspek process, alur pendaftaran peserta dibantu petugas dan diberikan surat rujukan balik lalu ke puskesmas dengan kondisi stabil, sedangkan surat elijibilitas juga dapat dilihat dari bukti kepesertaan, namun petugas kurang memahami bentuk surat elijibilitas. Sebagai kesimpulan, aspek input bermasalah pada kurangnya man, material dan machines yang menyebabkan terganggunya aspek process seperti kurang optimalnya kinerja pengelola program rujukan balik dalam memberikan pelayanan. Kata kunci: program rujuk balik; penyakit kronis; input; process